A placebo-controlled trial of nadolol in the treatment of neuroleptic-induced akathisia. - Wells BG; Cold JA; Marken PA; Brown CS; Chu CC; Johnson RP; Nasdahl CS; Ayubi MA; Knott DH; Arheart KL (The Journal of clinical psychiatry, 1991)
BACKGROUND: Although propranolol has been documented to be useful in treatment of neuroleptic-induced akathisia, preliminary anecdotal reports on the efficacy of nadolol in treatment of this condition are contradictory. METHOD: To evaluate the efficacy of nadolol in treatment of this condition, a double-blind, placebo-controlled trial was conducted in 20 psychiatric inpatients. Patients with akathisia of at least moderate severity were randomly assigned to receive nadolol 40 to 80 mg/day or placebo. Patients were rated daily for 4 days, then every other day for 15 days by means of the Extrapyramidal Symptom Rating Scale. RESULTS: No significant differences were found between or within groups in subjective restlessness scores. In objective akathisia scores, there were no significant differences between groups; however, beginning at Day 9, both groups showed significant improvement compared with Day 1. There was no difference between groups in number of responders. CONCLUSIONS: The authors' data do not support the efficacy of nadolol in the treatment of neuroleptic-induced akathisia and do not provide support for a peripheral site of action for beta-blockers in treatment of this condition.